EFFECTS OF COMMUNICATION, COLLABORATION, AND KNOWLEDGE CONSTRUCTION ON STUDENTS’ WORK READINESS WITH WORK MOTIVATION MODERATION - Dewi, Christine Natalia; Nurdian Susilowati (Universitas Muhammadiyah Surakarta, 2025)
Work readiness has become a crucial aspect of vocational education as students are increasingly required to master 21st-century competencies. This study aims to analyze the effects of communication skills, collaboration skills, and knowledge construction on the work readiness of vocational high school students, as well as to examine the role of work motivation as a moderating variable. This research addresses the limitations of previous studies that tend to examine these skills separately by integrating three 21st-century skills into a single research model with a moderating variable. A quantitative approach employing a survey method was used in this study, involving 207 students from five vocational programs at public vocational high schools in Semarang City. The data were analyzed using descriptive statistics, multiple regression analysis, and moderated regression analysis (MRA) with SPSS version 27. The results indicate that communication skills, collaboration skills, knowledge construction, and work motivation have a significant effect on students’ work readiness. Furthermore, work motivation strengthens the relationship between communication skills and work readiness, as well as between collaboration skills and work readiness; however, no moderating effect was found in the relationship between knowledge construction and work readiness. These findings emphasize that students’ work readiness is influenced not only by technical competencies but also by non-technical competencies (21st-century skills) and motivational factors. This study contributes theoretically to the development of an integrated model of students’ work readiness and provides practical implications for schools in strengthening soft skills–based learning and enhancing students’ work motivation.